Pendidikan dan Latihan Dasar Perkoperasian Angkatan II Tahun 2023: Urgensi, Implementasi dan Ukuran Capaian Promosi Anggota - Supriyadi, Deddy (LPPM Universitas Koperasi Indonesia, 2024)
Member Promotion topic was delivered at the 2023 Cooperative Training and Training Class II. The training participants were State Civil Apparatus (ASN). This material is presented to make participants understand what member promotion is, the importance of member promotion, and implementing and measuring its achievements. The training method is carried out using the andragogy education method and the